(untitled) (GEON Journal (Management, Organizations and Business), 2015)
The role played by the Territories face a dynamic and competent with growing developments world, forces us to devise elements that Captivate and sell through the design of identity, an image that effectively communicates the attributes and potentials of a region, since today more than ever, characteristics of origin are an aspect of much importance in consumer decision-making. So, as the concept and development of territorial marketing plan, provides elements and strategies for the promotion and positioning of the Nations, departments and cities; as part of the identification of territorial differentiators to create an integral image, enabling you to meet the needs of the Stakeholders (local, investors and tourists), improving the economic and social development of a territory. Therefore, this article presents the concept and stages to develop a territorial marketing plan